Sufentanil during anesthetic induction of remifentanil‐based total intravenous anesthesia: a randomized controlled trial - Menezes, Daniel C. (2019)
Background: Postoperative pain represents an important concern when remifentanil is used for total intravenous anesthesia because of its ultrashort half‐life. Longer acting opioids, such as sufentanil, have been used during induction of remifentanil‐based total intravenous anesthesia as a means to overcome this shortcoming. However, the effectiveness and safety of such strategy still lacks evidence from randomized clinical trials. Hence, we aimed to assess the postoperative analgesic efficacy and safety of a single dose of sufentanil administered during the induction of remifentanil‐based total intravenous anesthesia. Methods: Forty patients, scheduled for elective open abdominal surgery, were randomized to receive remifentanil‐based total intravenous anesthesia with or without a single dose of sufentanil upon induction. We assessed the postoperative morphine consumption administered through a patient‐controlled analgesia pump. Self‐reported pain scores and the occurrence of nausea, vomiting, pruritus, agitation, somnolence and respiratory depression were also assessed up to 2 days after surgery. Results: The mean difference between the sufentanil and control groups regarding morphine consumption in the post‐anesthetic care unit and at 12, 24 and 48 h after surgery were −7.2 mg (95%CI: −12.5 to −2.1, p < 0.001), −3.9 mg (95%CI: −11.9 to 4.7, p = 0.26), −0.6 mg (95%CI: (−12.7 to 12.7, p = 0.80), and −1.8 mg (95%CI: (−11.6 to 15.6, p = 0.94), respectively. Neither self‐reported pain nor the incidence of adverse events were significantly different between groups at any time point. Conclusion: Our findings suggest that the administration of sufentanil during induction of remifentanil‐based total intravenous anesthesia is associated with decreased early postoperative opioid consumption.